2019
DOI: 10.1098/rspb.2018.2934
|View full text |Cite
|
Sign up to set email alerts
|

The pursuit strategy of predatory bluefish (Pomatomus saltatrix)

Abstract: A predator’s ability to capture prey depends critically on how it coordinates its approach in response to a prey’s motion. Flying insects, bats and raptors are capable of capturing prey with a strategy known as parallel navigation, which allows a predator to move directly towards the anticipated point of interception. It is unclear if predators using other modes of locomotion are employing this strategy when pursuing evasive prey. Using kinematic measurements and mathematical modelling, we tested whether bluef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…Section 4 applies PAM to a case study of the pursuit tactics of bluefish predators and §5 uses the methodology on a case study on the evasion tactics of zebrafish prey. Although the primary data analysed in these two cases is based on two previous experimental studies [28,29], the results reported here can be verified using the statistical data provided in this work. Section 6 summarizes the results and describes ongoing work.…”
Section: Introductionsupporting
confidence: 70%
“…Section 4 applies PAM to a case study of the pursuit tactics of bluefish predators and §5 uses the methodology on a case study on the evasion tactics of zebrafish prey. Although the primary data analysed in these two cases is based on two previous experimental studies [28,29], the results reported here can be verified using the statistical data provided in this work. Section 6 summarizes the results and describes ongoing work.…”
Section: Introductionsupporting
confidence: 70%
“…Therefore, we could straightforwardly derive the optimal 117 prediction rule adopted by predators by using a straight line ( figure 1c). This is similar to 118 interception strategies which have been observed in birds, bats, fishes, and insects [31][32][33][34][35]. The 119 predicted position can be described as follows: 120…”
Section: Lévy Walks With µ = 11 and 30 Correspond Approximately To supporting
confidence: 63%
“…In hoverflies Eristalis and Volucella , males use their innate knowledge of female’s size to compute the optimum interception angle based on the combination of position and angular speed of the target 26 . Other species maintain the bias angle constant throughout the pursuits such as Bluefish Pomatomus saltatrix , who keeps a 10° horizontal bias angle 27 . Dragonflies use a biased pursuit strategy in the vertical plane to hold the target image in the dorsal acute zone, a crescent of a particularly high resolution about 55° above the eye equator.…”
Section: Introductionmentioning
confidence: 99%